(untitled) (Journal of Business Management and Accounting, 2021)
The aim of this paper is to evaluate the size of the public sector (based on percentage of public sector expenditures to Gross Domestic Product (GDP) and percentage of public sector revenues to GDP) of Malaysia and compare it with other Associations of Southeast Asian Nations (ASEAN) countries. This study utilised a descriptive approach to compare the size of Malaysian public sector with other ASEAN countries (Brunei, Cambodia, Indonesia, Laos, the Philippines, Thailand, and Vietnam). The data were retrieved from 2000 to 2014 (15 years) that involved examination of documents from Key Indicators of Developing Asian and Pacific Countries Reports. Findings revealed that Malaysia ranks number three in terms of the size of public sector among ASEAN countries. Findings also indicated that the Malaysian percentage of public sector expenditure to GDP is around 20% to 30% which is considered as optimal size for the public sector. Malaysia also shows a deficit budget for 2000 to 2014, and similar trends were reported for other ASEAN countries. Meanwhile, the limitations of this study are that it is descriptive in nature and does not test any relationships between variables. Hence, future research may take into account other factors such as economic growth and government efficiency, and test relationships with the size of the public sector.